Integrating a local CRIS with the PTCRIS synchronization ecosystem - Lopes, A. L. (2019)
The scientific community, in particular, and society, in general, should have easy access to the innovation and knowledge generated by scientific research. However, the multiplicity of existing science information systems and institutional repositories does not allow for a simple and fast propagation of the results of scientific activities. In that context, and under the dictum “Add once, reuse multiple times”, the PTCRIS initiative was started in 2014 with the goal of creating an integrated ecosystem for the propagation and synchronization of scientific information amongst multiple parties. This ecosystem, which includes the development of the PTCRSync framework, allows for different information systems to share and synchronize information amongst them, thus avoiding the duplication of efforts of the researchers that used to have to deposit the same information in several different systems. This paper describes the integration of the PTCRISync synchronization mechanism with the current research information system of ISCTE-Instituto Universitário de Lisboa, Ciência-IUL. The results and the impact of the implemented approach in terms of the quantified benefits for researchers and institutions are also presented.